Effect of the EndoBarrier Gastrointestinal Liner on obesity and type 2 diabetes: protocol for systematic review and meta-analysis of clinical studies - Rohde, Ulrich (BMJ Publishing Group, 2013)
INTRODUCTION: Obese patients with type 2 diabetes undergoing bariatric surgery experience significant and lasting weight loss and improved glycaemic control. However, bariatric surgical procedures such as Roux-en-Y gastric bypass are irreversible and associated with considerable short-term and long-term risks. The EndoBarrier Gastrointestinal Liner or duodenal-jejunal bypass sleeve (DJBS) is a fully reversible procedure that has been developed to treat obesity and type 2 diabetes. We aim to perform a systematic review and meta-analysis of safety and efficacy of DJBS. METHODS AND ANALYSES: A systematic review with meta-analysis (as per the preferred reporting items for systematic reviews and meta-analyses) of randomised controlled trials of the device (vs no intervention, sham and/or low-calorie diet) will be performed. Primary endpoints include change in body weight and glycated haemoglobin and safety. Secondary endpoints constitute changes in other glycaemic parameters and blood lipids and the proportion of patients discontinuing antidiabetic medication. MEDLINE, EMBASE, The Cochrane Library and Science Citation Index will be sought electronically along with manual searches. The primary meta-analysis will use random effects models due to an expected intertrial heterogeneity. Fixed effect meta-analysis will be executed to assess the impact of small trials. Dichotomous data will be analysed using risk difference and continuous data using weighted mean differences, both with 95% CIs. ETHICS AND DISSEMINATION: The study will describe the impact of DJBS on obesity and type 2 diabetes and possibly contribute to clinical decision-making. The results of this study will be disseminated by peer-reviewed publication and scientific presentations. REGISTRATION: PROSPERO CRD42013004819